Presentation of Tortor Bejan at Traditional Ceremonies of the Batak Toba Community - Martozet Martozet; Eszter Tari; Dilinar Adlin; Tania Rizqy Octaviani; Liza Maysuri (Universitas Negeri Medan, 2025)
Tortor Bejan is an activity performed in the traditional death ceremony known as Mambejan or Patortorhon Parangin. In this ritual, the deceased is symbolically brought to life in order to commemorate their life. This tradition was formerly performed once every five years and lasted for forty days. However, over time, Tortor Bejan is now performed only once a year and lasts for a single night. This study focuses on the presentation form of Tortor Bejan. The analysis employs Soedarsono’s theory of presentation, which defines dance presentation as the overall manner of performance, encompassing the main elements of a dance. The findings indicate that Tortor Mambejan is a ritual dance that symbolically revives ancestral spirits through a statue as a form of respect for ancestral contributions. Before the performance of Tortor Bejan, Tortor Mangaraksa Desa Nawalu is first performed by a male dancer. During the Bejan ritual, one highly respected ancestor is selected. If the ancestor passed away under the condition of Saur Matua, the Bejan statue must not be made of wood but from the ancestor’s bones. The dance is called Tortor Bejan because, during the performance, ancestral spirits are symbolically revived through a “kailit” statue known as Bejan. The performance of Tortor Bejan uses costumes made of Batak Toba ulos fabric with traditional makeup and is accompanied by Gondang Suling Ni Happang Na Opat and Gondang Sahala Raja.